Sosialisasi Kepada Masyarakat Tentang Daun Gamal Sebagai Pencegah Karies Gigi - Rina Asrina (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Cavities or dental caries are one of the chronic diseases of the mouth with the highest incidence rate. One way that can be used to prevent dental caries is to brush your teeth using toothpaste. The Gamal plant (Gliricidia sepium) can inhibit the growth of Staphylococcus aureus bacteria that cause dental caries. So far, people in Jennae Village only use Gamal Leaves as animal feed or as a hedge. The purpose of devotion is to provide socialization about Gamal leaves which can traditionally be used as a deterrent to dental caries by pounding and then rubbing them on the teeth. The community service method is counseling the community in the Jennae Village Office Hall, Liliriaja District, Soppeng Regency. The results of community service show that the people of Jennae Village have started using Gamal Leaf as a medicine to prevent dental caries based on the results of interviews with several residents through telephone lines and Whatsapp conversations, but they still use traditional methods.